Development of implantable MEMS for biomedical applications - Tng, Danny Jian Hang. (2012)
Despite the advancements made in conventional drug delivery over the years, there are many difficulties in the application of conventional drug delivery in the management of chronic diseases. There is a current need for develop treatment methods which are targeted and controllable to overcome some of the difficulties associated with conventional drug delivery. Due to their unique properties, Microelectromechanical systems (MEMS) Technology applications in implantable drug delivery systems have many advantages and are showing great promise in disease treatment. A key advantage of MEMS drug delivery devices is their small size and controllability. This project features a small, implantable, controllable drug delivery device which leverages on the strengths of conventional drugs, while providing the targeted and controllable features which they are lacking. The proposed device has: i) large drug reservoir ( ~100 μl) to minimize refilling, ii) relatively small in size (13mm x 13 mm x 4 mm), iii) a low power 3 V electrode for long-term, controlled electrochemical actuation, iv) a long targeted drug delivery cannula with a backflow valve, v) high flow rate of 0.4 μl/s at 3 V and vi) highly biocompatible.